Transatlantic Cooperation: Libya's Diplomatic Transformation - Baghat, Gawdat (Tufts Archival Research Center, 2005)
Volume 29, Issue 2. Summer Muammar al-Qadhafi's decision to denounce terrorism and rid Libya of weapons of mass destruction has changed Libyaï¿½s diplomatic status from a pariah to a responsible international player. Gawdat Bahgat thinks this will continue to affect Libyan foreign policy, as well as prospects for the Libyan oil industry.